Answer:
The GFC is 2
Step-by-step explanation:
Answer:
A. is correct so, -5
Step-by-step explanation:
Have a good day.
Step-by-step explanation:
what the f♤ck are those. any teachers give u it tell them to go do it
Hi there!
![\large\boxed{\text{At (-1, -2), }\frac{dy}{dx} = -\frac{2}{5}}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%5Ctext%7BAt%20%28-1%2C%20-2%29%2C%20%7D%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20-%5Cfrac%7B2%7D%7B5%7D%7D%7D)
![\large\boxed{\text{At (-1, 3), }\frac{dy}{dx} = -\frac{3}{5}}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%5Ctext%7BAt%20%28-1%2C%203%29%2C%20%7D%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20-%5Cfrac%7B3%7D%7B5%7D%7D%7D)
We can calculate dy/dx using implicit differentiation:
xy + y² = 6
Differentiate both sides. Remember to use the Product Rule for the "xy" term:
(1)y + x(dy/dx) + 2y(dy/dx) = 0
Move y to the opposite side:
x(dy/dx) + 2y(dy/dx) = -y
Factor out dy/dx:
dy/dx(x + 2y) = -y
Divide both sides by x + 2y:
dy/dx = -y/x + 2y
We need both x and y to find dy/dx, so plug in the given value of x into the original equation:
-1(y) + y² = 6
-y + y² = 6
y² - y - 6 = 0
(y - 3)(y + 2) = 0
Thus, y = -2 and 3.
We can calculate dy/dx at each point:
At y = -2: dy/dx = -(-2) / -1+ 2(-2) = -2/5.
At y = 3: dy/dx = -(3) / -1 + 2(3) = -3/5.
Answer:
yes
Step-by-step explanation:
yes that is true you are correct